2010
DOI: 10.1182/blood.v116.21.1371.1371
|View full text |Cite
|
Sign up to set email alerts
|

Unmutated IGHV1-69/D3-16/J3 Stereotyped HCDR3 Rearrangements (Subset 6) Are Associated with Indolent Disease Course and Have Outcome Independent of Mutational Status In Early Stage CLL (Rai 0)

Abstract: 1371 Background: IGHV1-69 gene identifies the most frequent IGHV gene in chronic lymphocytic leukemia (CLL) and identifies the paradigm of unmutated CLL (U-CLL), being used in roughly 1/3 U-CLL. It is often rearranged to form subsets of stereotyped HCDR3 patterns, likely selected and transformed from the natural naïve B-cell repertoire (Blood. 2010; 115:71-7). Being unmutated, IGHV1-69 CLL are hypothetically expected to have competent tumor B-cell receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…39,40 Our present results are in line with this observation, considering that CTLA4 expression was significantly higher in subset #6 vs. subset #8, in line with its less aggressive clinical behavior. 18 While in solid tumors TP63 mainly plays a pro-apoptotic and tumor-suppressive role, 41,42 its role in B cell neoplasia is unclear. Particularly for CLL, the two published studies reported opposing results, variably proposing TP63 as proapoptotic 51 or anti-apoptotic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 Our present results are in line with this observation, considering that CTLA4 expression was significantly higher in subset #6 vs. subset #8, in line with its less aggressive clinical behavior. 18 While in solid tumors TP63 mainly plays a pro-apoptotic and tumor-suppressive role, 41,42 its role in B cell neoplasia is unclear. Particularly for CLL, the two published studies reported opposing results, variably proposing TP63 as proapoptotic 51 or anti-apoptotic.…”
Section: Discussionmentioning
confidence: 99%
“…Our present results are in line with this observation, considering that CTLA4 expression was significantly higher in subset #6 vs . subset #8, in line with its less aggressive clinical behavior …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation